Object-oriented techniques (with Java) - Arora, Lalit Kishore; Bhatia, Raj Kumar (New Delhi, India : S.K. Kataria & Sons, 2010)
This book Object Oriented Technique with JAVA is written to serve as a textbook for B.Tech Vth semester students of Gautam Buddha Technical University. There are no prerequisites beyond a general familiarity with the ideas of computers and programs. There is enough materials for a full semester of college-level programming. This books has been divided into two parts: Part I is deals with Object-Oriented Techniques. The Object-Oriented Approach of software development based on modeling object from the real world. In this part we have also described implementation with modeling and design.
1. Introduction -- 2. Modeling -- 3. UML -- 4. Basic Structural Modeling -- 5. Basic Behavioural Modeling -- 6. Architectural Modeling -- 7. OMT Methodology -- 8. Introduction to Java -- 9. Beginning with Java Programs -- 10. Methods and Classes -- 11. Inheritance, Packages and Interfaces -- 12. Advance Programming Concepts -- 13. HTML and JAVA APPLET -- 14. Java Library -- 15. Java AWT -- 16. Event Handling -- 17. Software Development using Java -- 18. JDBC -- Bibliography -- Appendices -- Model Questions Papers -- Previous year Question Papers -- Index.
Includes bibliographical references and index.
Keywords: ORJECT-ORIENTED PROGRAMMING LANGUAGES